PENGARUH KEPEMIMPINAN DAN STRES KERJA TERHADAP KINERJA PEGAWAI RUMAH TAHANAN NEGARA (RUTAN) KLAS IIB SE-WILAYAH BANTEN - Ade Jaya Sutisna; Heryandi Heryandi (Universitas La Tansa Mashiro, 2020)
This research is quantitative research. The results of the study show that if leadership and work stress can affect the performance of employees in the Banten IIB Classroom Detention Center, leaders must evaluate the ways of leadership and minimize work stress and that can affect employee performance. The population of this study was all Class IIB State Detainees in the Banten region, totaling 207 people, 50 of whom were samples. The research instrument in the form of a questionnaire includes five alternative scale answers. The Leadership Questionnaire consists of 12 statements, 12 work stress statements, and 12 performance statements. The data analysis of the study was carried out by Normality Test and multiple linear regression. Hypothesis testing is done by t-test for individual influence and F-test for simultaneous effects. The study produced findings that: 1). There is a leadership effect on performance. This means, that is, when employees assess leadership it will have an impact on employee performance. And vice versa. 2) There is the influence of work stress on Performance. That is, the more the work stress level must be minimized, the better the work stress can improve employee performance. 3) There are influences from leadership and Job Stress on performance. This means that leadership and work stress together have an influence on performance.